Additional Insights Into Problem Definition and Positioning From Social Science; Comment on "Four Challenges That Global Health Networks Face" - Kathryn Quissell (Kerman University of Medical Sciences, 2018)
Commenting on a recent editorial in this journal which presented four challenges global health networks will have to tackle to be effective, this essay discusses why this type of analysis is important for global health scholars and practitioners, and why it is worth understanding and critically engaging with the complexities behind these challenges. Focusing on the topics of problem definition and positioning, I outline additional insights from social science theory to demonstrate how networks and network researchers can evaluate these processes, and how these processes contribute to better organizing, advocacy, and public health outcomes. This essay also raises multiple questions regarding these processes for future research.